The effect of retirement on obesity in women: Evidence from China - Hua-Lei Yang; Yi-Wen Tao; Si-Meng Cheng; Xiao-Qing Tang; Jin-Yan Cao; Dong-Fei Shen (Elsevier, 2023)
Introduction: Retirement has been shown to impact individual health as an important life course, and we examined the impact of retirement on the prevalence of obesity in women based on a female perspective. Methods: We use data from the five waves of the China Family Panel Study (CFPS) data from 2010 to 2018, with the body mass index (BMI) as the obesity measure. Fuzzy regression discontinuity design (FRDD) is used to overcome the endogeneity of retirement behavior and obesity. Results: After retirement, the obesity rate among women increased 23.8%-27.4% (p < 0.05). The mechanism is that the activity consumption has not changed significantly, but the energy intake has increased significantly. In addition, we found that the effect of retirement on female obesity was strong heterogeneity. Conclusions: The study found that retirement will increase the probability of obesity in women.